Consumed Foodstuffs Have a Crucial Impact on the Toxic Activity of Enteropathogenic Bacillus cereus - Riol, Claudia Da; Dietrich, Richard; Märtlbauer, Erwin; Jessberger, Nadja (Frontiers in Microbiology, 2018)
Enteropathogenic Bacillus cereus cause diarrhea due to the production of enterotoxins in the intestine. To start this process, spores have to be ingested together with contaminated food and survive the stomach passage. In this study, the influence of consumed foodstuffs on spore survival as well as on cytotoxicity towards colon epithelial cells was investigated. Spore survival of 20 enteropathogenic and apathogenic B. cereus strains during simulated stomach passage was highly strain-specific and did not correlate with the toxic potential. Survival of three tested strains was strain-specifically altered by milk products. Whereas milk, a follow-on formula and rice pudding had only little influence, spores seemed to be protected by milk products with high fat content such as whipped cream and mascarpone. Furthermore, tested milk products decreased the toxic activity of three B. cereus strains towards CaCo-2 cells. Investigating the individual components, lactoferrin, a skim milk powder and vitamins C, B5 and A showed the most inhibiting effects. On the other hand, biotin, vitamin B3 and another skim milk powder even enhanced cytotoxicity. Further studies suggested that these inhibiting effects result only partially from inhibiting cell binding, but rather from blocking the interaction between the single enterotoxin components.